PERAN PENDIDIK MENGEMBANGKAN FISIK MOTORIK ANAK USIA DINI DALAM PEMBELAJARAN MOTORIK - Wulandari Retnaningrum (JURNAL WARNA, 2021)
Early childhood is at the golden age. This age is a sensitive age. The most appropriate time to lay the foundation for developing abilities in all aspects of development. One of them is the motor skill which supports the development of other aspects. The basic movement abilities of early childhood include gross and fine motor movements that need to be stimulated and stimulated by educators in order to develop optimally and in accordance with the child’s developmental stage. But the fact that happened, there are still many educators who do not understand and know the concepts and benefits of motor learning for early childhood. Motor learning activities to develop gross and fine motor skills for early childhood emphasize hands on practice in the field. Educators do not understand and know how important its role is in developing children’s motor skills from an early age. As a professional educator, they should know their role in order to develop motor skills of early childhood to the fullest. Educators in developing early childhood motor skills must be able to act as motivators, facilitators, mentors, instructions and models. By knowing their role as educators, early childhood gross and fine motor development can develop optimally so that children can be better prepared to face the next life.